Calcium in the Pathophysiology of Atrial Fibrillation and Heart Failure - Denham, Nathan C.; Pearman, Charles M.; Caldwell, Jessica L.; Madders, George W. P.; Eisner, David A.; Trafford, Andrew W.; Dibb, Katharine M. (Frontiers in Physiology, 2018)
Atrial fibrillation (AF) is commonly associated with heart failure. A bidirectional relationship exists between the two - AF exacerbates heart failure causing a significant increase in heart failure symptoms, admissions to hospital and cardiovascular death, while pathological remodelling of the atria as a result of heart failure increases the risk of AF. A comprehensive understanding of the pathophysiology of AF is essential if we are to break this vicious circle. In this review, the latest evidence will be presented showing a fundamental role for calcium in both the induction and maintenance of AF. After outlining atrial electrophysiology and calcium handling, the role of calcium-dependent afterdepolarisations and atrial repolarisation alternans in triggering AF will be considered. The atrial response to rapid stimulation will be discussed, including the short-term protection from calcium overload in the form of calcium signalling silencing, but the eventual progression to diastolic calcium leak causing afterdepolarisations and the development an electrical substrate that perpetuates AF. The role of calcium in the bidirectional relationship between heart failure and AF will then be covered. The effects of heart failure on atrial calcium handling that promote AF will be reviewed, including effects on both atrial myocytes and the pulmonary veins, before the aspects of AF which exacerbate heart failure by are discussed. Finally, the limitations of human and animal studies will be explored allowing contextualisation of what are sometimes discordant results.